2018
DOI: 10.2174/1389450119666180703145410
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-based Nanocarriers for siRNA Delivery: Challenges, Strategies and the Lessons Learned from the DODAX: MO Liposomal System

Abstract: The possibility of using the RNA interference (RNAi) mechanisms in gene therapy was one of the scientific breakthroughs of the last century. Despite the extraordinary therapeutic potential of this approach, the need for an efficient gene carrier is hampering the translation of the RNAi technology to the clinical setting. Although a diversity of nanocarriers has been described, liposomes continue to be one of the most attractive siRNA vehicles due to their relatively low toxicity, facilitated siRNA complexation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 169 publications
0
13
0
Order By: Relevance
“… 2 Importantly, nanoparticle delivery can overcome many limitations of RNAi molecules by protecting them from degradation, facilitating cellular uptake, and preventing immune activation. 30 32 , 144 146 …”
Section: Strategies To Target Circrnasmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 Importantly, nanoparticle delivery can overcome many limitations of RNAi molecules by protecting them from degradation, facilitating cellular uptake, and preventing immune activation. 30 32 , 144 146 …”
Section: Strategies To Target Circrnasmentioning
confidence: 99%
“…Our lab has been using gold nanoparticles (AuNPs) as a delivery system in animal studies because they are highly stable, pure, and their surface is easy to modify. 144 , 147 We delivered AuNPs conjugated with siRNA targeting circDnmt1 or AON targeting binding sites on circDnmt1 for Auf1 and p53 proteins as a therapeutic approach for breast cancer. 15 We found that both treatments suppressed cellular autophagy and tumor growth and extended the lifespan of mice.…”
Section: Strategies To Target Circrnasmentioning
confidence: 99%
“…Lipid nanoparticles (LNPs) which contain siRNA and ionizable cationic lipids have proven to be effective in delivering gene materials to target sites. Some of them were proven to be effective in clinical trials (Oliveira et al, 2019;Xin et al, 2019). The ionizable cationic lipids such as heptatraconta-6,9,28,31-tetraene-19-yl 4-(dimethylamino) butanoate (Dlin-MC3-DMA) could provide a mechanism (acid dissociation constants below seven) to positively charge at low pH to entrap siRNA and keep neutral surface charges during circulation.…”
Section: Lipid Nanoparticlesmentioning
confidence: 99%
“…The toxicity of the lipid-based nanoparticles for delivery of siRNA is critical to turn research work to clinical applications. The toxicity of the lipid-based nanoparticles for siRNA delivery is mainly caused by usage of cationic lipids and also the immune response from siRNA (Tan, 2001;Bridge et al, 2003;Sledz et al, 2003;Soenen et al, 2009;Oliveira et al, 2019). siRNA can induce immune response to trigger interferon and inflammatory effect by the toll-like receptors (TLRs) such as TLR3 and TLR7, and the use of lipid-based nano vector may accelerate this activation to evoke unwanted side effects (Dass, 2002;Hornung et al, 2005;Kleinman et al, 2008).…”
Section: Potential Toxicity Induced By Nanoparticlesmentioning
confidence: 99%
“…Gene therapy requires the incorporation of genes, gene segments or oligonucleotides in nanocarriers that provide protection against enzyme-induced degradation and/or inactivation of the genetic material [8,87]. When used in cancer, the mechanism of action of this therapeutic strategy is based on: (i) deactivation of oncogenes; (ii) substitution of non-functioning tumor suppressor genes; (iii) inducing cell death or repair of normal cell function; (iv) defense of normal cells from drug-induced toxicity or activation of immune cells for the destruction of cancer cells [8,87]. The same favorable properties of GBNs for chemotherapy are valid for explaining their use in gene therapy.…”
Section: Chemotherapy and Gene Therapymentioning
confidence: 99%